Peningkatan Minat Baca Siswa Melalui Media Komik Berbasis Kearifan Lokal di Madrasah Ibtidaiyah Muhajirin Kota Jambi - Anggia Muharani; Saidah Ahmad (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to increase students' interest in reading using local wisdom-based comic media, in class III Madrasah Ibtidaiyah Muhajirin Jambi City. Students' reading interest is still relatively low in Natural and Social Sciences subjects, totaling 26 people. This research is a Classroom Action Research (PTK) with the Kemmis and Mc Taggart model consisting of 2 cycles. Data collection techniques used by researchers are observation, interviews, documentation and questionnaires. The results of this study indicate an increase in students' interest in reading by using comic media based on local wisdom with the percentage of the average value of students' interest in reading in the pre-cycle 33.13%, cycle I 67.45%, and cycle II 92.01% with a very high student interest category, and the percentage of student success in the pre-cycle 11%, cycle 1 61.53%, and cycle II 100% with a very high student interest category. As well as an increase in teacher and student activities in cycle 1 60% and cycle II 87.2%.